2011
DOI: 10.1111/j.1750-3841.2011.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Different Oils Used in Dough Formulation on the Lipid Fraction of Taralli

Abstract: An experimental investigation was carried out to evaluate the quality of taralli as a function of the type of oil used in their dough formulation. To this end, 4 types of oil (extra virgin olive oil, olive oil, olive-pomace oil, and refined palm oil) were utilized to prepare taralli to investigate on the lipid fraction degradation and evaluate the taralli acceptability by consumers. The data obtained pointed out that taralli manufactured with extra virgin olive oil were significantly more appreciated than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
2
4
1
Order By: Relevance
“…The obtained data were in agreement with the findings of Caponio and others (2011), who found that taralli made with extra virgin olive oil presented much lower contents of oxidation compounds than those made with refined oils. Thus, the use of extra virgin olive oil, a key element in the Mediterranean diet, could be an alternative to fats frequently used in such goods, while also raising the nutritional and health value (Visioli and others 2002).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained data were in agreement with the findings of Caponio and others (2011), who found that taralli made with extra virgin olive oil presented much lower contents of oxidation compounds than those made with refined oils. Thus, the use of extra virgin olive oil, a key element in the Mediterranean diet, could be an alternative to fats frequently used in such goods, while also raising the nutritional and health value (Visioli and others 2002).…”
Section: Resultssupporting
confidence: 92%
“…The determination of the free fatty acids (FFA) and peroxide value (PV) was carried out according to the Official Journal of the European Communities (1991). The fatty acid composition was determined by gas‐chromatographic analysis of fatty acid methyl esters, according to the official methods (Official Journal of the European Communities 1991, 1992), as described in Caponio and others (2011). The polar compounds (PC) of the oils were separated by silica gel column chromatography according to the AOAC method no.…”
Section: Methodsmentioning
confidence: 99%
“…Oleic acid (C18:1 n-9) contributed about 66% of the total fatty acids identified, followed by palmitic (C16:0; 15%) and linoleic (C18:2n-6; 13%) acids. Although the fatty acid profile of CTRL and enriched taralli is influenced by the lipid composition of wheat flour and vegetable oil used as ingredients, it was almost identical to that of taralli made with olive oil, as also reported by Caponio et al [22].…”
Section: Resultssupporting
confidence: 77%
“…Fats also influence the oxidative processes of food and then its shelf life. Caponio et al [21,22] and Giarnetti et al [23] reported that oil typology plays an important role in the formation and release of volatile aromas during taralli storage. The authors reported that volatile compounds increased during storage and that the content of individual volatile molecules was higher in taralli made with Extra-Virgin Olive Oil (EVOO) than refined oils.…”
Section: Introductionmentioning
confidence: 99%
“…The ingredients were weighed and kneaded for 2.30 min in an automatic kneader (Thermomix, Vorwerk, Germany). Subsequently, the dough was hand-blended and tarallini were formed and cooked at 230 °C for 20 min 17 to bake and dry the product. The tarallini were stored in closed glass jars, leaving for each sample the same head space, and stored at room temperature until analysis.…”
Section: Introductionmentioning
confidence: 99%